Development of phase change memory cell electrical circuit model for non-volatile multistate memory device - ElHassan, Nemat Hassan Ahmed (2017)
Phase change memory (PCM) is an emerging non-volatile memory technology that demonstrates promising performance characteristics. The presented research aims to study the feasibility of using resistive non-volatile PCM in embedded memory applications, and in bridging the performance gap in traditional memory hierarchy between volatile and non-volatile memories.